2022
DOI: 10.1007/s12209-022-00315-0
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Catalysts and Initiators for Promoting the Cracking of Endothermic Hydrocarbon Fuels

Abstract: Catalytic/initiated cracking of endothermic hydrocarbon fuels is an effective technology for cooling a hypersonic aircraft with a high Mach number (over 5). Catalysts and initiators can promote fuel cracking at low temperatures, increase fuel conversion and the heat sink capacity, and suppress coke deposition, thereby reducing waste heat. Catalysts mainly include metal oxide catalysts, noble metal catalysts and metal nanoparticles, zeolite catalysts, nanozeolite catalysts, and coating catalysts. Moreover, init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…In this work, the addition of initiators to the three co-cracking reaction systems was set to 2 wt % initiators/98 wt % hexane. The initiator addition of 2 wt % was considered effective in promoting hydrocarbon cracking. , It is worth emphasizing that initiators might crack to form olefins. In order to eliminate the influence of the self-cleavage of initiators, this work set the addition of initiators to account for only 2 wt % of the hydrocarbon while maintaining the same water content in each reaction system.…”
Section: Methodology Of Initiated Cracking Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the addition of initiators to the three co-cracking reaction systems was set to 2 wt % initiators/98 wt % hexane. The initiator addition of 2 wt % was considered effective in promoting hydrocarbon cracking. , It is worth emphasizing that initiators might crack to form olefins. In order to eliminate the influence of the self-cleavage of initiators, this work set the addition of initiators to account for only 2 wt % of the hydrocarbon while maintaining the same water content in each reaction system.…”
Section: Methodology Of Initiated Cracking Simulationmentioning
confidence: 99%
“…Still, the improvements in olefin products were not the focus, and a few initiators were believed to have an inhibitory effect on the production of olefins . Moreover, the application background of the above initiators was almost in the aerospace field . Aviation fuels were usually used under high pressure (3–5 MPa), and the temperature (500–700 °C) was relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…This approach facilitated a comprehensive evaluation of the quality of the prepared slices. The study by Liu (2022) employed a traditional, reliable, and stable liquid-phase method to determine the quality of Corni Fructus, which included morroniside, sweroside, loganin, gallic acid, 5-HMF, protocatechuic acid, and cornuside I. The biological activity results indicated that these seven chemical ingredients could be used as Q-markers for evaluating the quality of Corni Fructus.…”
Section: Q-marker Prediction Analysis Of Neuroprotective Effects Exer...mentioning
confidence: 99%
“…By engaging thirdparty rating agencies, commercial banks can engage independent third-party rating agencies to assess and rate the non-performing assets, increasing the credibility and impartiality of the credit ratings. Liu and Kang believe that this is due to the improvement of market support measures [12].…”
Section: Solution To Credit Enhancement In Commercial Bank's Non-perf...mentioning
confidence: 99%